2017
DOI: 10.1016/j.asmart.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Shorter recovery can be achieved from using walking boot after operative treatment of an ankle fracture

Abstract: Background/ObjectiveAnkle fractures, even if treated surgically, usually take a long time to heal. For all patients with ankle fracture, immobilisation is a critical part of treatment. Short-leg walking boots (WBs) have been reported to be an effective alternative to plaster casts (PCs) that could shorten this postoperative recuperative period. The aim of this study was to compare the functional recovery of a conventional PC with that of a WB after surgery for ankle fractures.MethodsForty-seven patients (mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…These complications include wound healing problems, redness, hyperthermia, superficial and deep infections, deep leg vein thrombosis, and loosening of the material resulting in a loss of reposition. Previous studies in elderly patients with preexisting comorbidities demonstrated that intramedullary nailing systems in distal fibula FX have a significantly lower incidence of soft tissue complications and lead to adequate FX stability compared to conventional plate osteosynthesis [ 26 , 28 , 29 , 30 ]. White et al described in their prospective randomized study on 100 patients ( n = 50 ORIF, n = 50 IM nailing) no superficial wound infections in the IM group compared to eight (16%) superficial wound infections in the ORIF group [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These complications include wound healing problems, redness, hyperthermia, superficial and deep infections, deep leg vein thrombosis, and loosening of the material resulting in a loss of reposition. Previous studies in elderly patients with preexisting comorbidities demonstrated that intramedullary nailing systems in distal fibula FX have a significantly lower incidence of soft tissue complications and lead to adequate FX stability compared to conventional plate osteosynthesis [ 26 , 28 , 29 , 30 ]. White et al described in their prospective randomized study on 100 patients ( n = 50 ORIF, n = 50 IM nailing) no superficial wound infections in the IM group compared to eight (16%) superficial wound infections in the ORIF group [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to fracture healing and the complications related to the surgery itself, postoperative therapy is a prognostic factor for the patient’s satisfaction, functional outcome, and return to normal daily activities [ 28 , 29 , 30 , 31 ]. For older patients suffering from an ankle fracture, returning to their normal daily life is important in terms of their quality of life and freedom [ 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strategic placement of the open and closed cell foam layers allows for a comfortable orthotic, due to it being well-cushioned, and shock resistant. Furthermore, the device is designed to be breathable and reduce the degree of discomfort experienced by the user, like commercial moon boots (Amaha, et al, 2017). The use of Velcro straps as the primary fasteners allows for the boot to be put on or removed easily, without requiring the assistance of a third party.…”
Section: Imentioning
confidence: 99%
“…The WB is used for acute injuries such as ligament sprains/tears, postoperative stabilization or support, ulcers, or cases with fractures [29,[32][33][34][35]. Amaha et al [36] in 2016 retrospectively evaluated patients who had surgeries for unstable ankle fractures. Of the 47 patients who received follow-up observations for at least 6 months, 25 wore a plaster cast (PC) and 22 wore a WB, and recovery rates were monitored in the two groups.…”
Section: Walking Boot (Controlled Ankle Movement Walker Aircast)mentioning
confidence: 99%